High willingness to use novel HIV and bacterial sexually transmitted infection partner notification, testing, and treatment strategies among gay and bisexual men - John, Steven A. (Sex Transm Infect, 2019)
OBJECTIVES: We sought to determine willingness of gay and bisexual men (GBM) to give HIV self-testing (HIVST) kits with patient-delivered partner therapy (PDPT) and engage in geosocial sexual networking (GSN) app-based partner notification. METHODS: A nationwide sample of GBM who self-tested HIV-negative (n=786) were asked about their willingness to give recent sex partners (main and casual) PDPT with an HIVST kit (PDPT+HIVST) after hypothetical bacterial sexually transmitted infection (BSTI) diagnosis. Men were also asked about their willingness to notify sexual partners met on GSN apps using an anonymous app function after BSTI diagnosis. We examined associations of relationship status and condomless anal sex with casual partners, recent BSTI diagnosis, and perceived risk of HIV on PDPT+HIVST and anonymous app-based partner notification willingness (dichotomized) using binary logistic regressions, adjusting for age, race/ethnicity, education, and US region. From the partner’s perspective after receiving an app-based referral, frequency measures were used to report intentions for obtaining subsequent HIV/BSTI counseling and testing, engaging in HIVST if provided a free voucher, and obtaining BSTI treatment from a pharmacy with prescription voucher. RESULTS: Most (90.1%) were willing to give PDPT+HIVST to recent sex partners after STI diagnosis, and nearly all (96.4%) were willing to notify sex partners met online using an anonymous function within GSN apps. Regardless of casual partner condomless anal sex engagement, partnered GBM had higher odds of reporting willingness to give PDPT+HIVST compared to single men who recently engaged in condomless anal sex with a casual partner. If anonymously notified via an app, 92.5% reported they would likely obtain counseling and testing, 92.8% would engage in HIVST if provided a free voucher, and 93.4% would obtain treatment from a pharmacy with prescription voucher. CONCLUSIONS: GBM generally found novel partner notification, testing, and treatment strategies acceptable, indicating the need for feasibility and cost-effectiveness evaluations.